Stability study of azithromycin in ophthalmic preparations - Andréia de Haro Moreno; Maria Fernanda Conz da Silva; Hérida Regina Nunes Salgado (Universidade de São Paulo, 2009)
A stability study of azithromycin in ophthalmic preparations was developed by submission to different types of light, temperature and pH, using the biodiffusion assay (cylinder 3 x 3) for the quantifications. Bacillus subtilis, ATCC 9372, was used as test organism. The used concentration range was of 50 to 200 µg/mL. The study demonstrated that the drug suffered degradation when submitted to the ultraviolet light, germicide light, solar luminosity, acid solution, basic solution and hydrogen peroxide solution. The results were analyzed by the analysis of variance (ANOVA). O estudo de estabilidade de azitromicina em preparações oftálmicas foi realizado após exposição a diferentes tipos de luz, temperatura e pH, utilizando o método de difusão em ágar (cilindros 3 x 3) para as quantificações. A faixa de concentração foi de 50 a 200 µg/mL. O estudo demonstrou que o fármaco sofreu degradação quando submetido às luzes ultravioleta, germicida e solar, e a soluções ácida, alcalina e de peróxido de hidrogênio. Os resultados foram analisados através da análise da variância (ANOVA).